Phenyl-substituted aminomethylene-bisphosphonates inhibit human P5C reductase and show antiproliferative activity against proline-hyperproducing tumour cells - Giuseppe Forlani; Giuseppe Sabbioni; Daniele Ragno; Davide Petrollino; Monica Borgatti (Taylor & Francis Group, 2021)
In certain cancers, such as breast, prostate and some lung and skin cancers, the gene for the enzyme catalysing the second and last step in proline synthesis, δ1-pyrroline-5-carboxylate (P5C) reductase, has been found upregulated. This leads to a higher proline content that exacerbates the effects of the so-called proline-P5C cycle, with tumour cells effectively using this method to increase cell survival. If a method of reducing or inhibiting P5C reductase could be discovered, it would provide new means of treating cancer. To address this point, the effect of some phenyl-substituted derivatives of aminomethylene-bisphosphonic acid, previously found to interfere with the catalytic activity of plant and bacterial P5C reductases, was evaluated in vitro on the human isoform 1 (PYCR1), expressed in E. coli and affinity purified. The 3.5-dibromophenyl- and 3.5-dichlorophenyl-derivatives showed a remarkable effectiveness, with IC50 values lower than 1 µM and a mechanism of competitive type against both P5C and NADPH. The actual occurrence in vivo of enzyme inhibition was assessed on myelogenous erythroleukemic K562 and epithelial breast cancer MDA-MB-231 cell lines, whose growth was progressively impaired by concentrations of the dibromo derivative ranging from 10−6 to 10−4 M. Interestingly, growth inhibition was not relieved by the exogenous supply of proline, suggesting that the effect relies on the interference with the proline-P5C cycle, and not on proline starvation.